Dampak Pengembangan Pariwisata Terhadap Perkembangan Usaha Mikro, Kecil Dan Menengah Di Kabupaten Magetan - Suyono, Bambang (Universitas Merdeka Madiun, 2020)
Abstractâ€” The objectives of this research are (1) to know the process of tourism development in Magetan Regency, especially the Sarangan Lake tourism area; (2) knowing the development of UMKM in the Sarangan Lake Tourism Area and the factors that influence it; and (3) knowing the impact of tourism development on the development of MSE seen from the increase in turnover and growth of MSE in Magetan Regency.The population in this study was the head and staff of the tourism office of Magetan Regency, amounting to 5 people and the micro and small entrepreneurs in Magetan Regency, amounting to 30 people. Data collection techniques in this study include interviews, observation and documentation. The analysis used is qualitative analysis, while the method used is descriptive qualitative.The findings of this study are (1) tourism development in Magetan Regency, especially Sarangan Lake tourism, is well managed, improvements in tourist objects are continuously carried out and new tourism potentials are explored to increase tourist visits; (2) the development of MSE in tourist areas, especially Sarangan Lake, is influenced by various factors including low human resources and an old mindset that still chooses to be a farmer compared to providing tourism services, limited capital which is only taken from private funds of business actors, offered monotony and minimal innovation and (3) successful tourism development resulting in increased tourist visits to Sarangan Lake in particular and other tourism objects in general, this has a positive impact on MSE. MSE as a means of tourism are able to develop along with the tourism development process.Â Keywordsâ€”: Tourism; Micro; Small and medium enterprises.